Blackened Futsal Tournament Management System - LOKMAN, MUHAMAD AKMAL IRFAN; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2026)
Futsal tournaments have gained popularity, yet many still rely on manual processes, such as pen and paper or spreadsheet-based systems that lead to inefficiencies and organizational issues. The primary issue is the absence of an integrated platform to run tournaments, which causes delays, chaos, and dissatisfaction among organisers, players, and fans. This project aims to develop the Blackened Futsal Tournament Management System to automate and streamline tasks such as scheduling, score tracking, and team management. The system was developed using the Prototyping Model and built with web technologies including HTML, CSS, JavaScript, PHP, and MySQL, with Stripe API integration for payments. Results show improved scheduling accuracy, real-time score updates, and enhanced communication among stakeholders. Findings suggest that digital automation significantly reduces administrative workload and improves the overall user experience. Future improvements may include mobile-native integration and broader support for multi-stage tournaments.